(a^2-b^2)(c^2-d^2)-4bcd
Answers
Answered by
1
pls mark as brainliest
Hi ,
It is given that ,
a² + b² - c² - d² + 2ab - 2cd
rearrange the terms ,
= a² + b² + 2ab - c² - d² - 2cd
= ( a² + b² + 2ab ) - ( c² + d² + 2cd )
= ( a + b )² - ( c + d )²
= [ ( a + b ) + ( c + d ) ][ ( a + b) - ( c + d ) ]
= ( a + b + c + d ) ( a + b - c - d )
I hope this helps you.
: )
Hi ,
It is given that ,
a² + b² - c² - d² + 2ab - 2cd
rearrange the terms ,
= a² + b² + 2ab - c² - d² - 2cd
= ( a² + b² + 2ab ) - ( c² + d² + 2cd )
= ( a + b )² - ( c + d )²
= [ ( a + b ) + ( c + d ) ][ ( a + b) - ( c + d ) ]
= ( a + b + c + d ) ( a + b - c - d )
I hope this helps you.
: )
urvashi74:
it's ok check question
Answered by
0
Answer:
Step-by-step explanation:
Similar questions
English,
7 months ago
CBSE BOARD X,
7 months ago
Math,
1 year ago
Social Sciences,
1 year ago
Hindi,
1 year ago
Math,
1 year ago
Hindi,
1 year ago